2012
DOI: 10.1016/j.dnarep.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Exo1 plays a major role in DNA end resection in humans and influences double-strand break repair and damage signaling decisions

Abstract: The resection of DNA double-strand breaks (DSBs) to generate ssDNA tails is a pivotal event in the cellular response to these breaks. In the two-step model of resection, primarily elucidated in yeast, initial resection by Mre11/CtIP is followed by extensive resection by two distinct pathways involving Exo1 or BLM/WRN/Dna2. However, resection pathways and their exact contributions in humans in vivo are not as clearly worked out as in yeast. Here, we examined the contribution of Exo1 to DNA end resection in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 50 publications
8
130
1
Order By: Relevance
“…Moreover, it has been demonstrated that WRN depletion leads to a marked reduction in the frequency of RPA and BrdU/ssDNA foci formed in response to ionizing radiation, indicative of a resection defect (52). A similar phenotype has been observed in DNA2-depleted cells (18).…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, it has been demonstrated that WRN depletion leads to a marked reduction in the frequency of RPA and BrdU/ssDNA foci formed in response to ionizing radiation, indicative of a resection defect (52). A similar phenotype has been observed in DNA2-depleted cells (18).…”
Section: Discussionmentioning
confidence: 50%
“…In line with this hypothesis, HP1α knockdown impairs both 53BP1 and BRCA1 recruitment to sites of damage. 17 Given that 53BP1 and BRCA1 have opposite effects on DNA-end resection, [30][31][32][33] further research on this particular issue would certainly be critical to shed light on the molecular details of HP1 role during this process.…”
Section: Discussionmentioning
confidence: 99%
“…To specifically monitor hExo1-dependent resection, we first measured resection in DNA2-depleted cells. DNA2-depleted cells displayed only a minor DNA resection defect (11,12). To define the role of hRPA on hExo1 resection, we next quantified DNA resection intermediates in cells that were depleted for both RPA2 and DNA2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, functionally deficient Exo1 variants have been identified in familial colorectal cancers, and Exo1-null mice exhibit a significant increase in tumor development, decreased lifespan, and sterility (8,9). Exo1 also promotes DSB repair via homologous recombination (HR) by processing the free DNA ends to generate kilobase-length ssDNA resection products (1,(10)(11)(12). The resulting ssDNA is paired with a homologous DNA sequence located on a sister chromatid, and the missing genetic information is then restored via DNA synthesis.…”
mentioning
confidence: 99%